Teatro de Santa Isabel: da polêmica construção ao esplendor da inauguração (1840 – 1850). - Palmeira, Rosemária de Assunção (2021)
In this report, we seek to present how the construction and inauguration of the Teatro de Santa Isabel took place, between the years 1840 and 1850, with a view to preparing a book as the final product of the research. We value for using our academic bias to think about how expectations, behaviors and codes of social interaction that were operationalized in this space, associated with an ideal of modernity, could show us how the Theater demarcated the construction of a new leisure space aimed at the wealthier in the capital of the province of Pernambuco. We privilege the relationships that existed and were perceived through the conflicts and expectations generated around this undertaking. Thus, we sought support, especially, in journalistic sources, Provincial Reports and Laws of the period and the Intimate Diary of the engineer Louis-Léger Vauthier. We consulted authors aligned with Cultural History and Social History. We reiterate that our research was materialized in a digital book which contains narratives, reflections, images and illustrations that present a historical-interpretative reading of the construction of the Santa Isabel Theater as an architectural and symbolic icon in nineteenth-century Recife.